Adherence to aspirin treatment during pregnancy - Fanney Sigurgeirsdóttir 1988- (2024)
This study aimed to investigate treatment adherence to aspirin among Icelandic pregnant individuals and how well they understand the purpose of aspirin use. Also, explore knowledge of risk factors and identify factors contributing to inadequate adherence to aspirin. Preeclampsia is a life-threatening disorder that is treated by delivery, sometimes before term. Aspirin treatment has been shown to effectively reduce the risk of preterm birth in cases of preeclampsia; however, good adherence is imperative. In Iceland, adherence to aspirin treatment and factors contributing to inadequate adherence are unknown. 843 participated, and the requirements were expecting a baby, having attended the first neonatal appointment, and fluency in Icelandic. The study is a cross-sectional internet survey, and participants answered questions about socio-demographics, pre-eclampsia-related information, and measures of medication adherence, anxiety, and depression. Participants also answered open-ended questions about aspirin use, adherence, and reasons for being advised to take aspirin. Results demonstrated high adherence to aspirin treatment, with no systematic demographic differences between fully adherent and less adherent groups. Anxiety and depression did not significantly differ between groups according to aspirin intake in the previous week. However, lower adherence was related to significantly higher depressive symptoms. Qualitative analysis showed that the most common reason for non-adherence was forgetfulness. Most individuals were aware of aspirin's role in preventing pre-eclampsia, but some lacked information or expressed uncertainty. In conclusion, this study found good adherence to aspirin among pregnant individuals in Iceland. Educational interventions to improve knowledge about pre-eclampsia and aspirin treatment and simple interventions such as daily reminders via apps or other technology could further enhance treatment. Keywords: pre-eclampsia, aspirin, adherence, pregnancy, Iceland